Resistance to Linezolid: Characterization of Mutations in rRNA and Comparison of Their Occurrences in Vancomycin-Resistant Enterococci - Prystowsky, Jason (American Society for Microbiology, 2001)
To assess the potential for emergence of resistance during the use of linezolid, we tested 10 clinical isolates of vancomycin-resistant enterococci (VRE) (four Enterococcus faecalis, five Enterococcus faecium, and one Enterococcus gallinarum) as well as a vancomycin-susceptible control (ATCC 29212) strain of E. faecalis. The enterococci were exposed to doubling dilutions of linezolid for 12 passes. After the final passage, the linezolid plate growing VRE contained a higher drug concentration with E. faecalis than with E. faecium. DNA sequencing of the 23S rRNA genes revealed that linezolid resistance in three E. faecalis isolates was associated with a guanine to uracil transversion at bp 2576, while the one E. faecium isolate for which the MIC was 16 μg/ml contained a guanine to adenine transition at bp 2505.